2018
DOI: 10.1021/acs.nanolett.8b02519
|View full text |Cite
|
Sign up to set email alerts
|

A Single Large Assembly with Dynamically Fluctuating Swarms of Gold Nanoparticles Formed by Trapping Laser

Abstract: Laser trapping has been utilized as tweezers to three-dimensionally trap nanoscale objects and has provided significant impacts in nanoscience and nanotechnology. The objects are immobilized at the position where the tightly focused laser beam is irradiated. Here, we report the swarming of gold nanoparticles in which component nanoparticles dynamically interact with each other, keeping their long interparticle distance around the trapping laser focus at a glass/solution interface. A pair of swarms are directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 52 publications
14
64
0
Order By: Relevance
“…To create large scale assemblies, we have to look beyond the conventional trapping methods and employ additional forces. To this end, various approaches have been utilized such as using plasmonic thin films (19,20), modulated light fields (21), Lorentz force between plasmons (22), light scattering of trapping laser by nanoparticles (6,23) and many more. One of the methods to assemble colloids is to utilize their temperature gradient dependent motility.…”
Section: Introductionmentioning
confidence: 99%
“…To create large scale assemblies, we have to look beyond the conventional trapping methods and employ additional forces. To this end, various approaches have been utilized such as using plasmonic thin films (19,20), modulated light fields (21), Lorentz force between plasmons (22), light scattering of trapping laser by nanoparticles (6,23) and many more. One of the methods to assemble colloids is to utilize their temperature gradient dependent motility.…”
Section: Introductionmentioning
confidence: 99%
“…When polystyrene NPs are trapped at the interface, a periodically aligned structure acts like a waveguide which allows the trapping laser to propagate and assemble more NPs beyond the focal spot [11,12]. A similar case is also observed for Au NPs, which form a dynamically fluctuating swarming assembly outside the focal spot [13]. For the initial stage, periodical structures (Yagi-Uda antenna like or hexagonal structures) are assembled inside the focal spot depending on the laser polarization (linear or circular, respectively).…”
Section: Introductionmentioning
confidence: 73%
“…Very recently, we found that a large number of Ag NPs illuminated by a linearly polarized laser beam could self‐assemble into partially ordered arrays, but they exhibited frequent structure transition among dimer chains, hexagonal NP lattice, and disordered structures . A similar study also found that a large assembly of Au NPs dynamically fluctuated in a focused laser beam with linear polarization . This dynamic behavior of light‐induced self‐assembly limits the fabrication of large‐scale optical matter with NPs.…”
Section: Introductionmentioning
confidence: 95%
“…Optical binding forces are interparticle forces arising from electrodynamic interactions between two or more polarizable particles illuminated by light, which lead to self‐arrangement of the particles into ordered structures (i.e., optical matter) . For example, plasmonic NPs can self‐assemble into optical matter chains and arrays with sub‐micrometer interparticle separations and high precision, but generally only a few NPs can form stable structures while an assembly of many NPs becomes unstable. Very recently, we found that a large number of Ag NPs illuminated by a linearly polarized laser beam could self‐assemble into partially ordered arrays, but they exhibited frequent structure transition among dimer chains, hexagonal NP lattice, and disordered structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation